Little elfie one - Jane, Pamela; Manning, Jane, 1960- (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2015)
Elves, snowmen, stars, and reindeer cavort at the North Pole on Christmas Eve, introducing the numbers one through ten.
Ages 4-8.
Keywords: Stories in rhyme; Christmas -- Fiction; Counting